Analysis of The Effect of Fuel Switching on The Thermal Efficiency of PLTG Unit 1.3 PT. PLN Indonesia Power Priok PGU - Ridwan, Muhammad; Adi Gumelar, Rachmat (Pelopor Publikasi Akademika, 2024)
This study discusses the topic of thermal efficiency analysis in gas turbines. This study aims to determine the effect of using LNG and HSD fuel on the value of thermal efficiency. Therefore, the actual brayton cycle calculation method is used. This research is doing data processing using software, namely Microsoft Excel, Engineering Equation Solver (EES) and Cycle Tempo. Based on the results of the calculations that have been carried out, the thermal efficiency at a load of 75 MW with LNG fuel is 37.96% to 44.62% at a load of 100 MW and with HSD fuel at a load of 75 MW it is 40.61% and 45.60% at a load of 100 MW. Then in the EES simulation results with LNG fuel at a load of 75 MW it is obtained 37.51%, and 41.96% at a load of 100 MW. whereas with HSD fuel at a load of 75 MW it was obtained 41.76% and 46.15% at a load of 100 MW, and also the results of the cycle tempo simulation with LNG fuel at a load of 75 MW were 32.56% to 37.43% at a load 100MW. Then with HSD fuel at a load of 75 MW it is 34.47% to 38.14% at a load of 100 MW